Development of an Operational Map for the 3D Printing of Phytosterol-Enriched Oleogels: Rheological Insights and Applications in Nutraceutical Design - María Itatí De Salvo; Camila Palla; Ivana M. Cotabarren (Foods)
Three-dimensional (3D) printing attracts significant interest in the food industry for its ability to create complex structures and customize nutritional content. Printing materials, or inks, are specially formulated for food or nutraceuticals. These inks must exhibit proper rheological properties to flow smoothly during printing and form stable final structures. This study evaluates the relationship between rheological properties and printability in phytosterol-enriched monoglyceride (MG) oleogel-based inks, intended for nutraceutical applications. Key rheological factors, including gelation temperature (Tg), elastic (G′) and viscous (G″) modulus, and viscosity (µ) behavior with shear rate (<semantics><mover accent="true">γ˙</mover></semantics>), were analyzed for their impact on flow behavior and post-extrusion stability. Furthermore, this study allowed the development of an operation map to predict successful printing based on material µ and Tg. Oleogels (OGs) were prepared with high-oleic sunflower oil (HOSO) and 10 wt% MG, enriched with phytosterols (PSs) at concentrations between 0 and 40 wt%. While higher PS content generally led to an increase in both Tg and µ, the 10 wt% PS mixture exhibited a different behavior, showing lower Tg and µ compared to the 0 wt% and 5 wt% PS mixtures. The optimal PS concentration was identified as 20 wt%, which exhibited optimal properties for 3D printing, with a Tg of 78.37 °C and µ values ranging from 0.013 to 0.032 Pa.s that yielded excellent flowability and adequate G′ (3.07 × 106 Pa) at room temperature for self-supporting capability. These characteristics, visualized on the operational map, suggest that 20% PS OGs meet ideal criteria for successful extrusion and layered deposition in 3D printing.